Sustainable denim fading using immobilized cellulase on reversibly soluble-insoluble polymers (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
This study introduces a sustainable approach to generic denim fabric washing by employing immobilized cellulase ontwo eco-friendly polymers (chitosan and Eudragit S-100). The immobilization process enhances the stability and reusabilityof cellulase, while the choice of chitosan and Eudragit S-100 allows for reversible solubility and insolubility, providing easyremoval of the enzyme after the washing process. The study investigates the enzymatic activity and stability of cellulasewhen immobilized on chitosan and Eudragit S-100 and assesses their efficiency in denim fading. The experimental resultsreveal that the immobilized cellulase exhibits some decreased activity with increased pH and thermal stability. Theimmobilized cellulase grades equivalent denim decolouration with reduced back-staining for three consecutive cycles incomparison to native cellulase which is drained after a single use. The proposed method not only addresses the economicconstraints of the reusability of enzymes but also contributes to the development of innovative and sustainable practices intextile industry.